2012
DOI: 10.1002/ece3.314
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive radiation in extremophilic Dorvilleidae (Annelida): diversification of a single colonizer or multiple independent lineages?

Abstract: Metazoan inhabitants of extreme environments typically evolved from forms found in less extreme habitats. Understanding the prevalence with which animals move into and ultimately thrive in extreme environments is critical to elucidating how complex life adapts to extreme conditions. Methane seep sediments along the Oregon and California margins have low oxygen and very high hydrogen sulfide levels, rendering them inhospitable to many life forms. Nonetheless, several closely related lineages of dorvilleid annel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…Moreover, 16S gene data split S. balaenophila into four distinct lineages, although with low divergence among them. Notably, 16S tends to have slower rates of substitution than other mtDNA genes (Thornhill et al, 2012;Brasier et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, 16S gene data split S. balaenophila into four distinct lineages, although with low divergence among them. Notably, 16S tends to have slower rates of substitution than other mtDNA genes (Thornhill et al, 2012;Brasier et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Some annelid taxa are particularly abundant and diverse at whale falls, such as dorvilleids, ampharetids and the boneeating worms Osedax (Vrijenhoek et al, 2009;Wiklund et al, 2012;Ravara et al, 2015;Eilertsen et al, 2017). The two former clades, also found in chemosynthetic-based ecosystems, demonstrate tolerance to toxic compounds and show trophic niche partitioning between species and genus, which it has been hypothesized to promote their high species diversity (Thornhill et al, 2012;Levin et al, 2013;Eilertsen et al, 2017). Alfaro-Lucas et al (2018) showed trophic niche partitioning between some hesionid species in a SW Atlantic whale fall.…”
Section: Discussionmentioning
confidence: 99%
“…Abundant and numerous species of Ophryotrocha usually inhabit whale-fall communities (Smith & Baco 2003, Wiklund et al 2009, 2012, Taboada et al 2013, Ravara et al 2015. In cold seeps, where many species of this genus also co-occur, trophic niche partitioning may partially facilitate coexistence (Levin et al 2003(Levin et al , 2013, as also hypothesized for whale falls (Thornhill et al 2012, Ravara et al 2015. Similarly, the hesionid Pleijelius sp., a higher consumer of chemosynthetic production, showed a marked difference in CDC compared to co-occurring and presumably omnivorous confamilial species Sirsoe cf.…”
Section: Discussionmentioning
confidence: 85%
“…Non-adaptive allopatric mechanisms may further include the founder effect (small isolates create starting gene pools for incipient species) and genetic drift of small populations, but sympatric hybridization should not be discarded when incipient species come together in a habitat patch. Evidence on multiple invasions of cold seeps and radiation via specialization and resource partitioning is provided for the genus Ophryotrocha [77,78]. This sulphide-tolerant polychaete is often represented by several sympatric species either in shallow reducing environments, deep-water seeps, or in different types of organic falls [14,77,79,80].…”
Section: Resultsmentioning
confidence: 99%